Artykuł recenzyjny (polemiczny) książki pod red. M. Nowaka pt. Rola prawa w systemie gospodarki przestrzennej - Marta Woźniak (Krytyka Prawa, 2023)
The article of a review character undertakes a polemic with the authors of the book edited by M. Nowak entitled The Role of the Law in the Spatial Management System on spatial planning and development presented from the perspective of the law. The authors undertook to present the role of law in the spatial management system, but they did so taking into account the fact that in spatial planning, apart from lawyers, there are also such participants as urban planners, city and landscape architects, officials and the public. In the book there are not only material legal accents embedded in the themes of environment, cultural landscape and monuments, but also procedural threads. There are issues of a general nature, concerning the role and interpretation of the law, interdisciplinary issues, reach ing into other sciences (economics, urban planning), specific issues (fee) and issues of a changing and dynamic nature (COVID-19 and spatial policy). The work strongly emphasises the axiological dimension with references to phrases such as public interest or common good. In good conscience, I recommend reading the book to all those interested in ‘planning law’ in the broadest sense of the term, and to those who prefer the intersection of legal and non-legal sciences. The book will also appeal to the academic community and the legal profession.